Sleep disturbances among young adult dual users of cigarettes and e-cigarettes: Analysis of the 2020 National Health Interview Survey - Laxmi Poudel; Amrit Baral; Alireza Abdshah; Kyle Grealis; Anurag Aka; Shreedhar Paudel; Denise C. Vidot (PLoS ONE, 2025)
Background The increasing use of conventional cigarettes and e-cigarettes among young adults (18-35 years) in the US raises significant health concerns, including impacts on sleep. While smoking’s adverse health effects are well-documented, the combined effects of conventional cigarette and e-cigarette use on sleep remain under explored, particularly in young adults. This study investigates the association between dual cigarette and e-cigarette use and sleep outcomes in a nationally representative US sample. Methods We utilized self-reported data from the 2020 National Health Interview Survey (NHIS) on young adults (N = 6128, Unweighted). Descriptive statistics and chi-squared tests and t-tests, where appropriate, compared socio-demographic, clinical, behavioral, and sleep-related characteristics by conventional cigarette/e-cigarette use status. Multinomial logistic regression estimated the odds of reporting short (<7 hours) or long sleep ( ≥ 9 hours) compared to normal sleep (7-8 hours) across different smoking categories. Result Of the total sample, 51.0% were females, mean age: 26.6 years (SD = 4.8). Cigarette smokers were the oldest (mean age 29.2 years), while e-cigarette users were the youngest (mean age 24.7 years) (p < .0001). Poor or long sleep was reported by 72.8% of cigarette smokers, 69.4% of e-cigarette users, and 71.9% of dual users (p < 0.001). Trouble falling asleep daily, or most days was reported by 49.9% of cigarette smokers, 63.6% of e-cigarette users, and 58.5% of dual users (p < 0.001). Difficulty staying asleep daily for most days was reported by 38.0% of cigarette smokers, 45.0% of e-cigarette users, and 44.6% of dual users (p < 0.0001). Furthermore, 13.7% of cigarette smokers, 5.9% of e-cigarette users, and 12.3% of dual users reported never waking up well-rested (p < 0.001). Multinomial logistic regression revealed that cigarette-only users (aOR:1.40, 95%CI:1.06-1.85), e-cigarette users (aOR:1.32, 95%CI:1.06-1.66), and dual users (aOR:1.81, 95%CI:1.46-2.24) had 40%, 32%, and 81% higher odds, respectively, of having poor sleep compared to non-users. Conclusion Cigarette and e-cigarette use is associated with poor sleep patterns and quality, with dual users having the greatest odds of having poor sleep outcomes among young adults.